1999
DOI: 10.1152/jn.1999.81.5.2243
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Receptive Field Properties of Thalamic Somatosensory Neurons by the Depth of Anesthesia

Abstract: Modulation of receptive field properties of thalamic somatosensory neurons by the depth of anesthesia. The dominant frequency of electrocorticographic (ECoG) recordings was used to determine the depth of halothane or urethan anesthesia while recording extracellular single-unit responses from thalamic ventral posterior medial (VPM) neurons. A piezoelectric stimulator was used to deflect individual whiskers to assess the peak onset latency, magnitude, probability of response, and receptive field (RF) size. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
264
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(284 citation statements)
references
References 39 publications
16
264
2
Order By: Relevance
“…Although it has been well demonstrated that the receptive field size of VPM neurons depends on the depth of anesthesia (Friedberg et al, 1999;Aguilar and Castro-Alamancos, 2005), this dependence seems to apply primarily to the more numerous relay cells forming the core of the barreloids, because cells within the head and tail compartments maintained a large receptive field despite the deep level of anesthesia used in our experiments. One should also note that, because barreloids form curved, obliquely oriented rods with respect to the vertical, different ratios of mono-whisker and multiwhisker cells can be obtained, depending on the location of microelectrode descents and on the extent to which the entire thickness of the VPM is explored.…”
Section: Discussionmentioning
confidence: 70%
“…Although it has been well demonstrated that the receptive field size of VPM neurons depends on the depth of anesthesia (Friedberg et al, 1999;Aguilar and Castro-Alamancos, 2005), this dependence seems to apply primarily to the more numerous relay cells forming the core of the barreloids, because cells within the head and tail compartments maintained a large receptive field despite the deep level of anesthesia used in our experiments. One should also note that, because barreloids form curved, obliquely oriented rods with respect to the vertical, different ratios of mono-whisker and multiwhisker cells can be obtained, depending on the location of microelectrode descents and on the extent to which the entire thickness of the VPM is explored.…”
Section: Discussionmentioning
confidence: 70%
“…Body temperature was maintained at 37°C with a feedback-actuated heating pad (Harvard Apparatus). Supplementary injections (10% of the initial dose) were given as needed to maintain the anesthesia at stage III-3 (Friedberg et al, 1999). After making a small opening in the dura mater, microelectrodes were advanced in columnar penetrations perpendicular to the cortical surface.…”
Section: Methodsmentioning
confidence: 99%
“…With the exception of the monoamine-containing cells (Einhorn et al, 1988; Pitts and Marwah, 1987), single-unit studies with iv COC delivery in anesthetized animals are limited and focused on slow drug-induced changes in discharge rate or neuronal responses to afferent inputs (Jimenes-Rivera and Waterhouse, 1991;Waterhouse et al, 1991). Urethane was chosen because this drug, compared to other general anesthetics, minimally inhibits brain metabolism, neuronal activity and responses to sensory stimuli (Buzsaki et al 1983;Friedberg et al 1999). Therefore, by comparing data obtained in the same animals in two preparations we were able to clarify the role of an animal's activity state in determining striatal neuronal responses to both somatosensory stimuli and COC.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%